Recombination between nonsegmented RNA genomes of murine coronaviruses. - Lai, M M (1985)
We have isolated a recombinant virus between the A59 and JHM strains of mouse hepatitis virus, which contain a single species of nonsegmented RNA genome. This recombinant was derived by mixed infection of DBT cells with temperature-sensitive mutants of A59 and JHM at nonpermissive temperature. Viruses recovered at this temperature were screened by oligonucleotide fingerprinting of their genomic RNAs. One recombinant virus, B1, was found to contain mostly A59-derived sequences, but the 3 kilobases at the 5' end of the genomic RNA was derived from JHM. Thus, the crossover point in the B1 genome is located within gene A, which codes for the viral RNA polymerases. The study of the intracellular RNA species of B1 virus revealed that probably all of the virus-specific subgenomic mRNA species contained the body sequences of strain A59 but the leader sequences of JHM. This result indicates that the JHM leader RNA, which differs from the A59 leader RNA, could be fused to the mRNAs of a different virus strain during RNA transcription. Furthermore, B1 virus-infected cells contain an additional subgenomic mRNA species which is transcribed from a new initiation site within gene C, suggesting that the leader RNA could determine the site of initiation for coronavirus mRNAs. These data represent a first report of RNA recombination between viruses, other than picornaviruses, which contain nonsegmented RNA genomes.